Thermoenvironomic evaluation of simple, intercooled, STIG, and ISTIG cycles - Kayadelen, Hasan Kayhan; Ust, Yasin (WILEY, 2018)
Low-technology cycle modifications available for improving gas turbine performance are still largely unexploited. Among those proven modifications, steam injection is found to be the most effective in boosting both the output capacity and thermal efficiency while reducing NOx emissions. It further improves part load performance under varying ambient conditions. Intercooling is another low-technology modification which can improve performance of simple and steam injected gas turbine cycles. Because of the uncertainties relating to an efficiency comparison of steam injected and simple cycle designs, the decision as to whether it is worthwhile to give more emphasis to steam injected cycles should be made on grounds other than efficiency alone. Therefore, this study comparatively evaluates simple, intercooled, steam injected (STIG), and intercooled steam injected (ISTIG) gas turbine cycles from the points of efficiency, network output, economics, and pollutant emissions using an advanced validated thermoenvironomic model. Optimum cycle parameters are investigated. Economic feasibility of steam injection and intercooling on simple and intercooled cycles are evaluated using an updated plant cost data. Total and environmental costs as well as profit of the plant owner are estimated for varying fuel costs and varying cycle parameters such as pressure, steam injection, and equivalence ratio. Results of our analysis based on the characteristic cycle parameters show that network output increases up to 22.2% and 14% respectively, when steam injection is implemented on simple and intercooled gas turbine cycles which correspond to up to 6.7% and 4.4% decrease in specific fuel consumption. Steam injection decreases NOx emissions of simple and intercooled cycles up to 67.2% and 65.2% respectively, and provides up to approximately 126.3% increase in net profit of intercooled cycle at the expense of an increase in total cost by 3.3%.
Keywords: economy; emissions; gas turbines; intercooling; performance; steam injection; thermoenvironomic analysis; GAS-TURBINE CYCLES; MULTI-CRITERION OPTIMIZATION; POWER-GENERATION; THERMODYNAMIC PROPERTIES; COMBUSTION PRODUCTS; EXERGY; MODEL; PLANT; Energy & Fuels; Nuclear Science & Technology